TINJAUAN MAQASHID SYARIAH Al-SYATIBI TENTANG PERLINDUNGAN HUKUM UMKM DI MASA PANDEMI - Rosiana Kholifah; Laili ‘Izza Syahriyati (Fakultas Syariah (Syari'ah Faculty ), 2020)
The purpose of this research is the protection of small, mid and medium Enterprise (SME) laws in pandemic where this pandemic affects many aspect, one of which is the economy. The economy as an important milestone in people's lives from small to large levels also has an important role in the State. Especially on the legal protection of SME in this pandemic period is urgently needed. As a badly affected SME business, the government is obliged to seek the welfare rights of SME, so that the Economic Activity of the State increases again. The guarantee of legal protection of SME during this pandemic is in accordance with the legislation or government regulations so that the role of SME is not weakened. This research is qualitative research using normative juridical approaches. The collection of data using books related to SME and Sharia Maqashid. The data is collected later with the concept of sharia maqashid Al-Syatibi. The results of the discussion show that economic activity will achieve significant benefits if it achieves the indicators in the Sharia maqashid al-Shatibi. First, the implementation of mental indicators (hifz Nafs) namely, the provision of facilities and assistance to resurrect the competitiveness capabilities of SME and property indicators (hifz mall) with the publication of Act Number 20 of 2008 year which specifically discusses about SME .